The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.26444/aaem/122409
|View full text |Cite
|
Sign up to set email alerts
|

Falls – the socio-economic and medical aspects important for developing prevention and treatment strategies

Abstract: Introduction.Although falls occur extremely frequently, they are still one of the least investigated causes of death. According to the World Health Organization, around 37.3 million falls occur globally every year resulting in the deaths of over 660,000 adults and almost 30,000 children.Objective. The aim of this review is to evaluate the most up-to-date and comprehensive knowledge on falls and their consequences, especially in populations at the highest risk of fatal falls. Brief description of state of knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Previous studies have reported low albumin levels and anemia as risk factors for falls in patients hospitalized in the acute phase, and these could be equally applied to patients with acute stroke. Finally, socioeconomic status, a well-known risk factor, was found to be unrelated to the in-hospital falls in this study [ 41 , 42 ]. These results were attributed to the reason that this study was conducted in a single region and incorporated only patients with acute stroke.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have reported low albumin levels and anemia as risk factors for falls in patients hospitalized in the acute phase, and these could be equally applied to patients with acute stroke. Finally, socioeconomic status, a well-known risk factor, was found to be unrelated to the in-hospital falls in this study [ 41 , 42 ]. These results were attributed to the reason that this study was conducted in a single region and incorporated only patients with acute stroke.…”
Section: Discussionmentioning
confidence: 89%
“…According to the World Health Organization (WHO), a fall can be understood as an event characterized by the sudden descent of the body to a level lower than the initial position [8]. 2 Additionally, patient falls contribute to prolonging the length of hospital stay, resulting in additional care costs and potentially having consequences for the institution's credibility and legal issues [9].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, fall history generates fear of a second fall, reducing progressively all the ADL resulting in social isolation, anxiety, and depression. This brings a substantial weakening of physical fitness that increases the fall risk, disability and hospitalization or institutionalization [4]. Fall events are also involved in driving up medical costs worldwide.…”
Section: Introductionmentioning
confidence: 99%